Research progress of additives in photobiological hydrogen production system to enhance biohydrogen. (October 2022) - Zhang, Quanguo; Liu, Hong; Shui, Xuenan; Li, Yameng; Zhang, Zhiping
Highlights: The effects of additives on biohydrogen production by photofermentation were reviewed. Appropriate amount of additives can promote photofermentation to produce hydrogen. Nitrogenase and hydrogenase are the direct causes of hydrogen production. Abstract: Photosynthetic biohydrogen has the advantages of extensive raw materials, clean and renewable, etc. But, its low substrate utilization rate limit its commercial application. It is reported that the use of additives in the process of biohydrogen by photofermentation is beneficial to increase biohydrogen. However, in practical application, the mechanism of additives in hydrogen production is not understood. This paper, the promotion effect of some additives on biohydrogen by photofermentation was reviewed. Whatever, the existing problems and development trends of various additives are also discussed. It is necessary to select appropriate additives according to the hydrogen-producing characteristics. The use of composite additives may further enhance biohydrogen, but the specific situation needs further exploration. The research results of this paper can help readers to further understand the role of additives in the crouse of photofermentative biohydrogen, provide reference for the research of photofermentative biohydrogen.